Implementasi Manajemen Bimbingan dan Konseling (POAC) untuk Pelayanan Bimbingan Konseling yang Efektif - Ifrah Hifsy; Firman; Neviyarni (Medan Resource Center, 2022)
Management is an effort or action to achieve goals through individual collaboration with groups with the support of other sources or facilities. Then in guidance and counseling there is also management, namely Planning, Organizing, Actuating and Controlling commonly called POAC. Which in POAC counseling affects the services to be carried out. If the POAC is carried out optimally, it will create an effective guidance and counseling service. Vice versa. If the POAC is not optimal, it will be difficult to create an effective service.